PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR - Sri Mulyo (UNIB Press, 2023)
The purpose of this study was to describe the application of the cretaive problem solving learning model in improving students' activity and achievement learning to improve student IPA learning achievement in class VI SD Negeri 03 Teras Terunjam. In this study, the Classroom Action Research (CAR) method was used and continued with experimental research. The subjects of this study were VI grade students of the SD Negeri in regions Teras Terunjam. The data collection techniques used in the study were the observation sheet and the student test method. The data analysis used values were of the ability to activity analysis, the pre-test and post-test analysis as well as the t test analysis of student learning achievement. The material validation instrument and students' activity in the study used was the likert scale model. The conclusions of this research are The application of creative problem solving learning can improve students' activity and improve student achievement in IPA study at SDN Gugus I Teras Terunjam for the 2022/2023, compared to conventional learning models